Experimental study on the effective range of FCM's fuzzifier values for web services' QoS data - Hasan, M.H. (Institute of Electrical and Electronics Engineers Inc., 2014)
The work presented in this paper is part of the development of a fuzzy Interval Type-2 (IT2)-based system. An IT2 system contains fuzzy type-2 membership functions that can be generated using a pair of FCM fuzzifier, m values. Evidences show that the effective range of m values is influenced by the underlying dataset. Hence, the objective of this paper is to present the experimental study on finding the effective range of m values for web services' QoS data. The study aimed at identifying range of m values that successfully generated Gaussian membership functions. As proposed by previous work, the experiment was carried out upon the m values in the range of 1.4 to 2.6. The works involved the datasets of three QoS parameters. The results showed that two of the datasets has the effective range of 1.7 to 2.6, while another one was 1.6 to 2.6. Â© 2014 IEEE.